HUBUNGAN KELENGKAPAN SUMBER BELAJAR DENGAN HASIL BELAJAR EKONOMI PADA SISWA KELAS X SEMESTER GENAP SMA NEGERI 7 BANDAR LAMPUNG TAHUN PELAJARAN 2015/2016 : INDONESIA - Kharisma Idola Arga; Tri Wahyudi; Desi Handayani (LPPM STIT PRINGSEWU, 2016)
Abstract This study aims to determine the completeness of the relationship of learning resources with improved learning outcomes, and the degree of closeness of the relationship between the completeness of the learning resources with improved learning outcomes of economic subjects in class X second semester. The method used in this research is descriptive quantitative method. Where a population of 397 students. The sample in this study as many as 38 students were given a test in the form of 20 multiple-choice questions to determine student learning outcomes and questionnaires to determine the relationship of the completeness of the source of student learning. Testing the hypothesis in this study using product moment correlation test. Based on the results of hypothesis testing that has been done with the author, obtained = 0.645 greater than rdaf at the level of 5% with N = 38 is 0.320 (statistics table) this means. Namely 0.645> 0.320, which means that there is a relationship completeness of learning resources with the results of the economic study in grade x second semester. Abstrak Penelitian ini bertujuan untuk mengetahui Hubungan kelengkapan sumber belajar dengan peningkatan hasil belajar, dan tingkat keeratan antara hubungan kelengkapan sumber belajar dengan peningkatan hasil belajar mata pelajaran ekonomi pada siswa kelas X semester genap. Metode yang dipakai dalam penelitian ini adalah metode deskriptif kuantitatif. Dimana populasi sebanyak 397 siswa. Sampel dalam penelitian ini sebanyak 38 siswa diberikan tes dalam bentuk pilihan ganda sebanyak 20 soal untuk mengetahui hasil belajar siswa dan angket untuk mengetahui hubungan kelengkapan sumber belajar siswa. Pengujian hipotesis dalam penelitian ini menggunakan uji korelasi product moment. Berdasarkan hasil pengujian hipotesis yang telah dilakukan penulis, di peroleh = 0,645 lebih besar dari rdaf pada taraf 5% dengan N = 38 yaitu 0,320 (tabel statistik) hal ini berarti . Yaitu 0,645 > 0,320 yang berarti bahwa ada hubungan kelengkapan sumber belajar dengan hasil belajar ekonomi pada siswa kelas x semester genap. Kata Kunci : kelengkapan sumber belajar dan hasil belajar